The first record of Jordanita (Solaniterna) subsolana (Staudinger, 1862) from Kazakhstan (Lepidoptera: Zygaenidae, Procridinae) - K. A. Efetov; S. A. Knyazev; E. E. Kucherenko (SHILAP)
Jordanita (Solaniterna) subsolana (Staudinger, 1862) was discovered in eastern Kazakhstan using the sex attractant EFETOV-2 (2-butyl 2-dodecenoate) synthesised in the Crimean Federal University. This is the first record of J. (S.) subsolana from Kazakhstan. As this species is now found on the border of Kazakhstan and China, most probably that J. (S.) subsolana is also present in China. An overview of the Zygaenidae fauna of Kazakhstan is presented.